2017
DOI: 10.18182/tjf.308944
|View full text |Cite
|
Sign up to set email alerts
|

Effect of boron compounds on the thermal and combustion properties of wood-plastic composites

Abstract: Bu çalışmada, atık lignoselülozik maddelerle üretilen odun plastik kompozitlerin termal özellikleri ve yangına karşı dirençleri araştırılmıştır. Bu amaç için lignoselülozik atıklar, yüksek yoğunluklu polietilen (YYPE), sodyum borat (boraks) ve borik asit kullanılmıştır. Kompozit malzemesinin üretimi aşamasında çift vida ekstruder kullanılmıştır. Elde edilen granül malzeme 175 °C'de preste preslenerek levha haline getirilmiştir. Yapılan testlertde farklı oranlarda odun plastik kompozitlere eklenen borik asit ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 11 publications
1
10
0
Order By: Relevance
“…It has been reported that the addition of a mixture of 16% borax and boric acid to the composite material reduced the burning rate by 30%. 20…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that the addition of a mixture of 16% borax and boric acid to the composite material reduced the burning rate by 30%. 20…”
Section: Resultsmentioning
confidence: 99%
“…Compared to the control composite, the charring rates increased by 20% and 40% for 3 and 5 wt% BxBc composites, respectively. Altuntaşet al 20 used a mixture of boric acid and borax to increase the fire resistance of the wood sawdust reinforced HDPE matrix composite. Their results are well consistent with our study.…”
Section: Effect Of Boron-based Fire-retardant Fillers On the Thermal ...mentioning
confidence: 99%
See 1 more Smart Citation
“…A study using BX+BA shows that the addition of fire retardant decreases burning rate in a wood plastic composite (Altuntaş et al 2017). Another paper showed that the reduction of the burning rate was around 50% compared to the control sample on wood flour filled high-density polyethylene composite (Donmez Cavdar et al 2015).…”
Section: Athens Journal Of Technology and Engineeringmentioning
confidence: 99%
“…Thermal and fire retardant effects of boric acid and borax on wood-plastic composites were investigated by Altuntaş et al According to the obtained TGA results, in case of amount of boron compound increases in the composite material, the decomposition temperatures of both the lignocellulosic material and the plastic material increase [8].…”
Section: Introductionmentioning
confidence: 99%